2002
DOI: 10.1093/annonc/mdf002
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine in metastatic nasopharyngeal carcinoma of the undifferentiated type

Abstract: Gemcitabine has moderate activity in NPC with minimal toxicity, and is also an effective salvage agent for patients who have failed or progressed after treatment with other agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(85 citation statements)
references
References 15 publications
1
84
0
Order By: Relevance
“…Based on the response rates and their associated CIs, Foo et al (2002) concluded that gemcitabine has moderately high singleagent activity in NPC of the undifferentiated type whether as a first-line or as a salvage treatment. They comment that, while it appears that those who had prior treatment seemed to respond better to gemcitabine, this can possibly be explained by patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the response rates and their associated CIs, Foo et al (2002) concluded that gemcitabine has moderately high singleagent activity in NPC of the undifferentiated type whether as a first-line or as a salvage treatment. They comment that, while it appears that those who had prior treatment seemed to respond better to gemcitabine, this can possibly be explained by patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…However, the duration of response is short, and median overall survival in these trials was on average approximately one year (range: 11 -25 mo). Two trials of non-platinum based monotherapy (gemcitabine 39 and capecitabine 40 ) were associated with worse overall response rates (28% and 37%, respectively) and similar median overall survival (7.2 and 14 months, respectively). Adding vinorelbine to gemcitabine for patients with platinum-resistant disease yielded an overall response rate of 36% with a median overall survival of 11.9 months 41 .…”
Section: Chemotherapy For Recurrent and Metastatic Diseasementioning
confidence: 98%
“…GEM-containing regimens have demonstrated tolerable toxicity profiles and encouraging efficacy in bladder cancer, breast cancer, non-small cell lung cancer and pancreatic cancer (22). GEM-based regimens are also commonly used in metastatic and recurrent NPC (23)(24)(25), and exhibit a moderately high activity with tolerable toxicity profiles in patients with NPC who are resistant to CDDP (26). CDDP is an important component of chemotherapy regimens for NPC.…”
Section: Introductionmentioning
confidence: 99%